A New Frame for Surgery of the Lumbar Spine - Tajima, Naoya; Kawano, Keiichiro; Matsumoto, Koichi; Deguchi, Yoshihiro; Morita, Shinji (Orthopedics & Traumatology, 1985)
A new frame is designed for back surgery. The frame consists of three supports (sternum and anterior superior iliac spines). The iliac crest is positioned at the center of the support, and hips and knees are semi-flexed. If the frame gives adequate support with suitable adjustment, the lumbar area of the back of the patient is a flat plane, his abdomen hangs free, and his femoral vessels and inferior vena cava are not compressed. Oxygen intake and vital capacity were measured on seven healthy men and intraosseous pressure in the spinous process of the lumbar spine on another seven patients in this frame and other type five frames. It may be concluded as follows: (1) the patient can be made comfortable, (2) there is no restriction to chest and abdomen, and (3) there is no congestion of the epidural venous plexus.